AB0479 Characterisation of the effect of renal impairment on upadacitinib pharmacokinetics. (12th June 2018) - Mohamed, M.-E.F.; Coppola, S.; Feng, T.; Anderson, J.; Othman, A.A.
Abstract : Background: Upadacitinib is a selective inhibitor of Janus kinase 1 (JAK1) which is currently being evaluated for the treatment of several autoimmune disorders, including rheumatoid arthritis (RA). Although renal elimination plays a minor role in upadacitinib clearance (<20% of upadacitinib dose is eliminated unchanged in urine), a considerable number of RA patients have renal dysfunction. As such, characterisation of the effect of different degrees of renal impairment on upadacitinib plasma exposures is important for this patient population. Objectives: The objective of this study was to assess the pharmacokinetics of upadacitinib in subjects with mild, moderate, and severe renal impairment compared to subjects with normal renal function. Methods: This Phase 1 study was conducted in 24 adult subjects, who were assigned to one of four groups (six subjects per group) according to the estimated glomerular filtration rate (eGFR) as calculated by the Modification of Diet in Renal Disease (MDRD) equation: normal renal function (eGFR of ≥90 mL/min/1.73 m 2 ), mild renal impairment (60–89 mL/min/1.73 m 2 ), moderate renal impairment (30–59 mL/min/1.73 m 2 ), and severe renal impairment (15–29 mL/min/1.73 m 2 ). Subjects received a single 15 mg dose of upadacitinib extended-release formulation under fasting conditions. Blood samples for pharmacokinetic assessments were collected for 120 hours after dosing. The effect of renal impairment on upadacitinib plasma exposures was assessed through regression analysis as well as analysis of covariance across the renal impairment categories. Results: The point estimates for upadacitinib plasma exposure ratios [90% confidence interval] in subjects with mild, moderate, and severe renal impairment were 1.18 [1.06–1.32], 1.33 [1.11–1.59], and 1.44 [1.14–1.82] for AUC and 1.06 [0.92–1.23], 1.11 [0.88–1.40], and 1.14 [0.84–1.56] for Cmax, respectively, relative to subjects with normal renal function. In this analysis, one subject with moderate renal function showed exposures significantly lower than subjects with normal renal function. This subject was excluded to ensure a conservative estimate of the impact of renal impairment on upadacitinib exposure. Results from the categorical analysis were consistent with the results from the primary regression analysis. Conclusions: Renal impairment has only a limited effect on upadacitinib pharmacokinetics. Upadacitinib mean plasma exposures (AUC) in subjects with severe renal impairment are within 44% of mean exposures in subjects with normal renal function. This is in agreement with the known limited role of urinary excretion in upadacitinib elimination. Acknowledgements: The studies presented were funded by AbbVie. AbbVie contributed to the study design, research, and interpretation of data, reviewing, and approving the publication. All authors are employees and shareholders of AbbVie. Disclosure of Interest: M.-E. Mohamed Shareholder of: AbbVie, Employee of: AbbVie, S. Coppola Shareholder of: AbbVie, Employee of: AbbVie, T. Feng Shareholder of: AbbVie, Employee of: AbbVie, J. Anderson Shareholder of: AbbVie, Employee of: AbbVie, A. Othman Shareholder of: AbbVie, Employee of: AbbVie